2022
DOI: 10.1371/journal.pone.0264307
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of blood from autoimmune hepatitis patients reveals potential mechanisms with implications for management

Abstract: Autoimmune hepatitis (AIH) is a poorly understood, chronic disease, for which corticosteroids are still the mainstay of therapy and most patients undergo liver biopsy to obtain a diagnosis. We aimed to determine if there was a transcriptomic signature of AIH in the peripheral blood and investigate underlying biologic pathways revealed by gene expression analysis. Whole blood RNA from 75 AIH patients and 25 healthy volunteers was extracted and sequenced. Differential gene expression analysis revealed 249 genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Nevertheless, in IFN-alpha-mediated inflammation, CD200R can amplify the immune response ( 51 ). Type I interferon activation is also described for AIH ( 52 ), and it is likely that IBT triggers the induction of IFN-alpha. With regard to immunotherapies and their increasing use in combination with local ablative therapies, the CD200–CD200R axis is of major importance and additional investigations are needed to identify targets harmonizing combinations of both therapy types.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, in IFN-alpha-mediated inflammation, CD200R can amplify the immune response ( 51 ). Type I interferon activation is also described for AIH ( 52 ), and it is likely that IBT triggers the induction of IFN-alpha. With regard to immunotherapies and their increasing use in combination with local ablative therapies, the CD200–CD200R axis is of major importance and additional investigations are needed to identify targets harmonizing combinations of both therapy types.…”
Section: Discussionmentioning
confidence: 98%
“…Gene expression, proteomic, and metabolomic data come mainly from peripheral blood and single cohorts. More specifically, a recent study has shown that ML can discriminate between AIH and healthy controls based on gene expression profiles (92). A similar situation exists for microbiota, despite the growing interest on this side (93,94).…”
Section: Integrative Multi-omicsmentioning
confidence: 88%